A panel of 16 full-length HCV genomes was characterized in China belonging to genotypes 1 to 6 including subtype 2f and two novel genotype 6 variants - Xu, Ru (2013)
In this study, we characterized the full-length genomes of 16 HCV isolates obtained from patients in a single hospital in China using overlapping PCR followed by DNA sequencing. The obtained genomes are 9,414-9,628 nucleotides in length, and each genome contains a single ORF of 9,021-9,102 nucleotides. Nine genomes represent the common subtypes 1a, 1b, 2a, 2b, 3a, 3b, and 6a, while seven represent the infrequent lineages 1c, 2f, 4d, and 5a, and two novel genotype 6 variants. GZ51969 and GZ52540 are subtype 1b isolates belonging to two unique clusters designated A and B, which account for 29.5% and 59.5% of the 1b infections in China, respectively. ZS542 and GZ98799 represent the first two complete genomes of the provisionally assigned subtype 2f. ZS96 and ZS202 are novel genotype 6 variants that may qualify for two new subtypes. ZS17, ZS537, and ZS631 represent three alien subtypes, namely, 1c, 4d, and 5a, which were detected in China for the first time in this study and may have been recently introduced as a result of globalization. Taken together, these results confirmed a large variety of HCV taxonomic lineages in China through the sequencing of their full-length genomes. These lineages represent six genotypes, 11 subtypes, and two novel variants. They were characterized for achieving a better understanding of the HCV genetic variation patterns and for possible future research applications.